The relative condition factor and the Length-weight relationship of Otolithes ruber (Schneider, 1801) from the Iraqi marine waters - Al-Zaidy, Faleh M. (Mesopotamian Journal of Marine Sciences, 2020)
Relative condition factor (Kn) and the relationship of length-weight (L-WR) of Tiger Tooth Croaker fish Otolithes ruber (Schneider, 1801) were determined from January to August 2017 in the Iraqi marine waters. L-WR data of the fishes (females and males) were calculated separately. The mean of (Kn) for females and males was 1.04 and 0.999, respectively. The value of (Kn) for the females was minimum in January (0.953) and May (0.969), whereas the maximum value was noticed in March (1.06 for females and 1.058 for males). The b value was recorded at 2.9747 for the males and 3.0546 for the females. The results of the statistical t-test showed no significant differences between females and males (t= -0.6021, 1.222, p≤ 0.05, respectively).